Multifunctional scaffolds for bone tissue engineering and in situ drug delivery - Mouriño, V.; Cattalini, J. P.; Li, Wenjie; Boccaccini, Aldo R.; Lucangioli, S. (Elsevier Inc., 2014)
This chapter provides an overview about the development of bone tissue engineering scaffolds with the ability to provide the controlled delivery of therapeutic drugs. Typical drugs considered include gentamicin and other antibiotics generally used to combat osteomyelitis as well as anti-inflammatory drugs and bisphosphonates. Special attention has been given to the technology used for controlling the release of the loaded drugs. A detailed summary of drugs included in bone tissue scaffolds is presented and the many approaches developed to combine organic and inorganic biomaterials in composites for drug-delivery systems are discussed. The remaining challenges in the field are summarized, suggesting also future research directions.
CRIS-Team Scopus Importer:2022-08-05
Keywords: Bone tissue engineering; Drug delivery; Multifunctional scaffolds; Therapeutic drugs